ANALISIS IMPLEMENTASI REKAM MEDIS ELEKTRONIK BERDASARKAN FAKTOR HOT-FIT DI PUSKESMAS KAWALU KOTA TASIKMALAYA TAHUN 2023 - Rusdiana, Ari; Yogaswara, Dadan; Annashr, Nissa Noor (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Regulation of the Minister of Health Number 24 of 2022 explains that health services including public health center must organize electronic medical records. The implementation of electronic medical records at Kawalu Public Health Center is still constrained. The purpose of this study was to analyze electronic medical records implementation based on human, organization and technology – benefit factors. This type of research was descriptive qualitative with 13 informants. Data collection techniques were in-depth interviews, observation, document review, and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions with source triangulation and technical triangulation. The results of the study showed that in human factors, the skills of health workers in operating electronic medical records systems were uneven. In organizational factors, the support has not optimized for for facilities, human resources, policies, and structures. In the technology factor, the integration of E-Puskesmas data is only internally and has not been integrated externally, and the contents of the electronic medical records form do not contain patient consent data on health services. It is recommended that the Kawalu Public Health Center coordinate with the Health Office to hold technical guidance, prioritize the budget for computer procurement, complete the preparation of standard operational procedures, form a medical record review team, register the information system, coordinate with providers to adjust data and integrate with the satusehat platform.